Innovation in Sharia Business Management for Sustainability and Sharia Compliance: An Islamic Legal Approach - Arifyanto, Gatot Teguh; Ginting, Rika Githamala; Dari, Suci Wulan (Program Pascasarjana UIN Sumatera Utara, 2025)
This research discusses innovations in sharia business management that aim to achieve sustainability and conformity with sharia principles through an Islamic legal approach. The main focus of this research is to explore the application of sharia principles in business management that can support sustainability and ensure compliance with Islamic law while still paying attention to ethical aspects and social responsibility. The method used is an in-depth literature study on various references related to managerial innovation in sharia business. The results of the study show that companies that apply the principles of sustainability and social responsibility in accordance with sharia can achieve a competitive advantage, increase consumer loyalty, and have a positive impact on society and the environment. The study also recommends that Islamic companies increase training and education related to Islamic law to reduce challenges in the application of these principles.